The Correlation Between the Emotional Intelligence and Attitude Toward Educational Field and Job Prospects in Midwifery Students of Tehran City in 2018 - Abbasi Fashami, Mahta; Kariman, Nourossadat; Ahmad Pourkeivani, Elham; Sadat Rahnemaie, Fatameh; Rashidi Fakari, Farzaneh; Nasiri, Malihe (Advances in Nursing & Midwifery, 2020)
Introduction: Students’ attitudes toward their educational field and job prospects are significantly necessary for their educational system. Midwifery is one of the essential fields in health, and students of this field are the pillars of protecting health in the future. This research aims at the determination of the relationship between emotional intelligence and attitude toward the educational field and job prospects in Midwifery students. Methods: This research was conducted as descriptive-sectional research with 251 midwifery bachelor students in the universities of medical sciences in Tehran city in 2018. The sampling method includes three inventories of demographic information, attitude toward the educational field, job prospects, and emotional intelligence. Statistical data were analyzed using SPSS (vr.16) software. Results: 57.8% and 62.9% of people neither agree nor disagree about the midwifery field and job prospects of this field, respectively. The positive correlation was observed between emotional intelligence and self-management with the educational field and job prospects. There was a negative relationship between the educational years of the spouse with an attitude toward the educational field. The negative relationship was observed between the educational year, mean high school average, and the mark of attitude toward the job prospects. Conclusions: Although most midwifery students are interested in this field and job, some wrong decisions and policy-makings have disappointed them. It is essential to change policies and make significant decisions according to the significant role of the midwife in the health and necessity of motivation in the present and future performance of students.